Certification of ERM‐EB400, the First Matrix Reference Material for Lead Isotope Amount Ratios, and ERM‐AE142, a Lead Solution Providing a Lead Isotopic Composition at the Edge of Natural Variation. Issue 1 (29th January 2019) - Vogl, Jochen; Yim, Yong‐Hyeon; Lee, Kyoung‐Seok; Goenaga‐Infante, Heidi; Malinovskiy, Dmitriy; Hill, Sarah; Ren, Tongxiang; Wang, Jun; Vocke, Robert D.; Murphy, Karen E.; Nonose, Naoko; Rienitz, Olaf; et al.
Abstract : Lead isotope amount ratios are commonly used in diverse fields such as archaeometry, geochemistry and forensic science. Currently, five reference materials with certified lead isotope amount ratios are available, namely NIST SRM 981, 982 and 983, GBW‐04442 and NMIJ 3681‐a. Only NIST SRM 981 and NMIJ 3681‐a have approximately natural isotopic compositions, and NIST SRM 981 is predominantly used for correcting mass discrimination/mass fractionation in the applied mass spectrometric procedures. Consequently, there is no other certified reference material available to be used for validation and/or quality control of the analytical procedures applied to lead isotope amount ratio measurements. To fill this gap, two new reference materials have been produced and certified for their lead isotope amount ratios. For both certified reference materials, complete uncertainty budgets have been calculated and SI traceability has been established. This provides the users with independent means for validating and verifying their analytical procedures and for conducting quality control measures. ERM‐EB400 is a bronze material with a nominal lead mass fraction of 45 mg kg −1 and certified lead isotope amount ratios of n ( 206 Pb)/ n ( 204 Pb) = 18.072(17) mol mol −1, n ( 207 Pb)/ n ( 204 Pb) = 15.578(18) mol mol −1 and n ( 208 Pb)/ n ( 204 Pb) = 38.075(46) mol mol −1 with the associated expanded uncertainties ( k = 2) given in brackets. ERM‐AE142 is a high‐purity solution of lead in 2% nitric acid with a nominal mass fraction of 100 mg kg −1 and certified Pb isotope amount ratios of n ( 206 Pb)/ n ( 204 Pb) = 21.114(17) mol mol −1, n ( 207 Pb)/ n ( 204 Pb) = 15.944(17) mol mol −1 and n ( 208 Pb)/ n ( 204 Pb) = 39.850(44) mol mol −1 with the associated expanded uncertainties ( k = 2) given in brackets. Both materials are specifically designed to fall within the natural lead isotopic variation and to assist users with the validation and verification of their analytical procedures. Note that while one of these reference materials requires the chemical separation of Pb from its matrix (ERM‐EB400), the other does not (ERM‐AE142). As additional information, δ 208/206 PbNIST SRM 981 values are provided for both materials. For ERM‐AE142, a delta value of δ 208/206 PbNIST SRM 981 = −28.21(30)‰ was obtained, and for ERM‐EB400, a delta value of δ 208/206 PbNIST SRM 981 = −129.47(38)‰ was obtained, with the associated expanded uncertainties ( k = 2) given in brackets. Key Points: First matrix reference material certified for lead isotope ratios. Together with a solution based reference material a set of isotope reference materials is available to test and validate analytical procedures for lead isotope ratio analysis. Associated relative expanded uncertainties are < 0.12% for all isotope ratios.